Inventory of specimens from the paleovertebrates collections of Museu Nacional/UFRJ and Museu de Ciências da Terra/DNPM submmited to digital techniques - Rehem, Caroline; Sobral, Gabriela; Romano, Pedro Seyferth R; Grillo, Orlando N.; Carvalho, Luciana B.; Henriques, Deise D. R.; Azevedo, Sergio Alex K. (Anuário do Instituto de Geociências, 2007)
Abstract